Hospital discharge planning in cardiac care: study protocol for a mixed-methods study on the implementation, influencing factors and quality of care in Germany - Imhof, Lena; Bartels, Raphaele; Blum, Karl; Blume, Kai Svane; Fleischer, Steffen; Gottschalk, Susan; Heber, Robin; Horenkamp-Sonntag, Dirk; Meyer, Gabriele; Remppis, Bjoern Andrew; Schneider, Udo; Schreyoegg, Jonas; et al. (BMJ open, 2025)
IntroductionDischarge planning (DP) is essential to ensure continuity of care during patient transitions between inpatient and outpatient settings. Although DP has been legally required for all hospitals in Germany since 2017, several studies show considerable variation in its implementation, likely due to differences in structural characteristics and organisational processes. Both quality and efficiency-enhancing DP processes are particularly important in the context of cardiovascular disease, which is the leading cause of mortality and a major contributor to healthcare costs in Germany. The ‘Ready to Discharge’ (R2D) project investigates the implementation status, influencing factors and outcomes of DP in cardiac units of German hospitals. By integrating quantitative and qualitative data, we aim to identify best practices and provide actionable recommendations for improving DP processes.Methods and analysisA mixed-methods study design will be used. Quantitative analyses will be based on primary data from hospital and patient surveys combined with secondary data from health insurance claims and hospital quality reports. Key outcome measures will include healthcare utilisation outcomes (eg, readmissions, emergency department visits), patient health status outcomes (eg, patient satisfaction, self-rated health) and medication-related outcomes (eg, medication adherence). Qualitative interviews with healthcare professionals will enrich the findings by providing insights into barriers and facilitators to DP.Ethics and disseminationThis study was approved by the Ethics Committee of Bergische University of Wuppertal and the German Federal Office for Social Security. Informed consent will be obtained for all primary data collections. Hospital managing directors will be informed prior to the hospital survey and will be able to withdraw consent. Patients can withdraw their consent at any time. Secondary data will be analysed in pseudonymised form to ensure patient confidentiality. Results will be disseminated through workshops, regional and international conferences and peer-reviewed publications.